System identification and active vibration control of a flexible structure - de Abreu, Gustavo Luiz C. M. [UNESP] (2012)
The aim of this paper is to illustrate the active control of vibration of a flexible structure using a model-based digital controller. The state-space model of the system is derived using a system identification technique known as the Observer/Kalman Filter Identification (OKID) method together with Eigensystem Realization Algorithm (ERA). Based on the measured response of the structure to a random input, an explicit state-space model of the equivalent linear system is determined. The model is used in a Linear Quadratic Regulator (LQR) to control the first two modes of vibration of a cantilever beam using a piezoelectric actuator/sensor pair. Experimental results demonstrate the efficacy of the proposed approach.